Fluidic Engineering: Investigating Cutting Fluids’ Effect on Machined Surface Roughness - T.R. Vijayaram; Ananth Padmanabhan; Y. Yaswanth; K. Bhavani Chandra; G. Yaswanth; A.S.V. Sarma (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
The primary goal of this experimental study project is to determine the optimal cutting fluid by experimenting with two distinct oil kinds and compositions. Thirty-six compositions of cutting oil are obtained by mixing three distinct oil compositions, such as mineral oil and paraffin oil, with six different additive and anti-foaming agent compositions. Then, using a trial-and-error methodology, we employed these 36 cutting oil compositions for drilling operations with constant pressure and speed. We used a syringe to inject the cutting fluids. A syringe allows for the accurate administration of cutting fluids. The main objective of this experimental study is to precisely identify the best cutting fluid for machining operations in order to maximize machining results by improving surface finish quality. The goal of this experimental study project is to determine the best cutting fluid to use when machining in order to enhance surface finish.
Keywords: Cutting oil; Fluidic Engineering; Surface roughness; fluids; metal